1986
DOI: 10.18174/njas.v34i2.16799
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of cadmium, lead, mercury and arsenic from feed into milk and various tissues of dairy cows: chemical and pathological data.

Abstract: In the 1st trial, lasting 3 months, 24 cows in 2 groups were given daily 15 kg roughage and 3 kg concentrates without (control) or with soluble compounds of heavy metals (including As2O5) added to the concentrates to give Cd, Pb, Hg and As at 2, 50, 0.2 and 3.4 (control) and 152, 200, 1.7 and 33 mg/day (treatment) resp. In the 2nd trial, lasting 2-3 lactations, 32 cows in 4 groups were kept indoors and given daily 10 kg roughage and 10-11 kg concentrates without or with soluble compounds (including As2O3), har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 3 publications
2
29
1
4
Order By: Relevance
“…The relatively high degree of Cd accumulation in liver and kidney as observed in the present study has previously been reported for many species including ruminants (13,14,16,31,32). The activity concentrations of 203 Hg in important food chain tissues were in the order muscle < liver < kidney.…”
Section: Discussionsupporting
confidence: 83%
“…The relatively high degree of Cd accumulation in liver and kidney as observed in the present study has previously been reported for many species including ruminants (13,14,16,31,32). The activity concentrations of 203 Hg in important food chain tissues were in the order muscle < liver < kidney.…”
Section: Discussionsupporting
confidence: 83%
“…The lack of significant tissue pathology or changes in body size was likely due to the relatively low levels of trace elements accumulated in raccoons in this study. Although we found significantly greater concentrations of Cu, As, Se, and Pb in animals from the contaminated site than in the reference site, the reported values were well below values associated with ex situ studies whose aims were to determine the physiological impairments resulting from toxic concentrations of Cu in sheep (1900 ppm) (Eisler 1998 ), As in domestic livestock (5–10 ppm) (Vreman et al 1986 ), and Se in horse (44 ppm) (Eisler 1985 ).…”
Section: Discussioncontrasting
confidence: 74%
“…Pour le Zn, des concentrations généralement équivalentes entre le muscle et le foie ont pu être observées (Bertrand et al 1981, Lisk et al 1982, Bruce et al 2003, Cai et al 2009. Sur le long terme, le Pb est connu pour être séquestré dans les os et peut être remobilisé (par exemple lorsque une femelle est en gestation ou allaite son petit) pour être redistribué contrairement au Cd qui reste majoritairement séquestré au niveau des reins (Pattee 1984, Vreman et al 1986, Scheuhammer 1996, Wilkinson et al 2003b, Khalafalla et al 2011, Abduljaleel et Shuhaimi-Othman 2013.…”
Section: D) Niveaux De Transfert Des Polluants Inorganiques Potentielunclassified
“…La concentration en Cd dans les reins du porc serait également 2 à 3 fois supérieure que dans le foie (Sharma et al 1979) Giulio et Scanlon 1984). Cependant ces résultats doivent être interprétés avec précaution car il semblerait que les concentrations puissent être soumises à un effet dilution entre le foie et le rein et dépendre de la taille des organes (Vreman et al 1986). Laurent et al (2005) ont synthétisé les données de différents travaux et calculé les FBC pour différents éléments.…”
Section: D) Niveaux De Transfert Des Polluants Inorganiques Potentielunclassified